Sistem Informasi Sarana Pendaftaran Digital SPP-IRT Berbasis Web di Dinas Kesehatan Kabupaten Bandung Barat - Rizky Muhammad Fauzi; Feri Sulianta (Syntax Idea, 2022)
West Bandung Regency Health Department is one of the government sectors responsible for supporting communities in coaching, serving, and monitoring West Bandung's health sector. One of them is the application service (SPP-IRT) for certification of food production in the domestic industry. applications, applicants have to go t o the West Bandung Regency Health Department to find out how to submit the application and obtain information from the results of the SPP-IRT application process. to facilitate application and information provision, it is necessary to have a useful system for the submission of applications and information from the SPP-IRT application process to be submitted online, to facilitate food production registration and can see the results of the submission process. In this study, managing submission data for application submission facilities and information from the results of the submission process so that business actors can apply for SPP-IRT online so that business actors no longer need to submit directly to the Health Department.